An Exploratory Study on the Knowledge Gap in Public Affairs among Kenyans. Issue 4 (2nd October 2018) - Ireri, Kioko; Roberts, Alex; Ochieng, Jimmy
Abstract: The current exploratory survey examines the knowledge gap hypothesis in the context of Kenya ( n =1, 000). Using education as an indicator of socioeconomic status (SES), the study explores the overall knowledge on public affairs among people in Nairobi, Kenya's capital. Also, in line with the knowledge gap hypothesis, the study investigates whether Kenyans of high SES are more knowledgeable about public affair than those of low SES. Relatedly, the research examines the variance on public affairs knowledge when compared by gender and local public affairs vs. international topics. The findings confirm the knowledge gap theory hypothesis. When analysed by demographics, male Kenyans are more knowledgeable about public affairs (72%) than their female colleagues (64%). In terms of marital status, married Kenyans appear more knowledgeable, while Protestants and Roman Catholic members recorded higher scores in public affairs than other religious groupings. By topics, Kenyans are more highly conversant with local public affairs (75%) compared to international topics (56%).